'Eighteen just makes you a person with certain privileges': the perspectives of Australian Sudanese and South Sudanese youths regarding the transition to adulthood. Issue 2 (4th March 2022) - Macaulay, Luke; Deppeler, Joanne
ABSTRACT: How the transition to adulthood is understood by youths can be influenced by social context and cultural background/s. Employing a voice-centred relational methodology approach, underpinned by a framework of identity and belonging, this paper reports on one aspect of a larger qualitative study designed to better understand the transition to adulthood as experienced by Australian Sudanese and South Sudanese youths. The findings of this study suggest that the perspectives on the transition to adulthood held by participants were based on feelings of possessing certain character traits and values they associated with the identity 'adult'. These findings are relatively consistent with previous research. Yet, the utility and value of this transition was also presented by participants as being inherently collective (i.e. to contribute within one's community). However, several barriers relating to social belonging were identified by participants to influence, and in some instances, impede a successful transition to adulthood.